Fecal Carriage of Staphylococcus aureus in the Hospital and Community Setting: A Systematic Review - Claassen-Weitz, Shantelle; Shittu, Adebayo O.; Ngwarai, Michelle R.; Thabane, Lehana; Nicol, Mark P.; Kaba, Mamadou (Frontiers in Microbiology, 2016)
Background and rationale: Staphylococcus aureus faecal carriage has been identified as a potential source for nosocomial transmission and a risk factor for disease development. This systematic review determined the overall S. aureus (including methicillin susceptible and resistant S. aureus (MSSA and MRSA)) faecal carriage rates within the community and healthcare settings. Methodology: Peer-reviewed articles indexed in Medline, Scopus, Academic Search Premier, Africa-Wide Information, CINAHL, and Web of Science were identified using applicable and controlled vocabulary through to 11 November 2015. Eligible studies were ascertained by three independent reviewers. Random-effects meta-analyses of proportions were performed to determine S. aureus, MSSA and MRSA faecal carriage rates reported by eligible studies. Results: Twenty six studies were included in this review. The pooled estimates for S. aureus, MSSA and MRSA faecal carriage were 26 % (95 % confidence interval (CI): 16.8 % - 36.3 %), 86 % (95 % confidence interval (CI): 65.9 % - 97.9 %) and 10 % (95 % CI: 0.7 % - 27.0 %), respectively. Faecal S. aureus carriage rates increased on average from 10 % to 65 % during the first eight weeks of life, followed by an average carriage rate of 64 % at six months and 46 % at one year of life. Genotyping techniques were employed mainly in studies conducted in developed countries and comprised largely of gel-based techniques. Six studies reported on the role of S. aureus faecal strains in diarrhoea (n = 2) and the risk for acquiring infections (n = 4). Eight of the 26 studies included in this review performed antibiotic susceptibility testing of S. aureus faecal isolates. Conclusion: This study provides evidence that screening for S. aureus faecal carriage, at least in populations at high risk, could be an effective measure for the prevention of S. aureus transmission and infection in the healthcare and community setting. More well-structured studies need to be conducted and sequence-based genotyping techniques should be employed for the comparison of isolates on a global scale in both developing and developed countries.